Capsaicin-loaded vesicular systems designed for enhancing localized delivery for psoriasis therapy. (2nd April 2016) - Gupta, Ruchi; Gupta, Madhu; Mangal, Sharad; Agrawal, Udita; Vyas, Suresh Prasad
Abstract : The aim of the current investigation is to evaluate the potential of capsaicin (CAP)-containing liposomes, niosomes and emulsomes in providing localized and controlled delivery, to improve the topical delivery of drug. CAP-bearing systems were prepared by the film hydration method and compared through various in vitro and in vivo parameters. The TEM photographs suggested that the carrier systems were spherical in shape and nanometric in size range. Skin retention studies of CAP from in vitro and in vivo experiments revealed significantly higher accumulation of drug in the case of the emul-gel formulation. Based on the results, we concluded that the emul-gel may be a potential approach for the topical delivery of CAP, for an effective therapy for psoriasis.